Prophylactic Treatment of Children with Hemophilia in Sweden - Ljung, Rolf (Seminars in Thrombosis and Hemostasis, 2024)
Hemophilia A/B are caused by deficiency or lack of coagulation factors VIII (FVIII) or factor IX (FIX), respectively, in plasma. A person with hemophilia develops bleeding in the joints and muscles at an early age, which, if left untreated, leads to early arthropathy. Preventive treatment can be achieved by regular (prophylactic) administration of FVIII/FIX. In 1958, this was implemented on a small scale in Sweden with FVIII in patients with severe hemophilia A, and in those with hemophilia B in 1972 when FIX became available. However, there were problems with human immunodeficiency virus and hepatitis infection from contaminated blood products. In the 1990s, recombinant FVIII and FIX concentrates were introduced. The major remaining problems then were the development of inhibitors, and the need for a venous route for the injections in very young children. High-titer inhibitors were treated by immune tolerance induction according to a modified model of the original Bonn high-dose protocol. A central venous line, i.e., Port-A-Cath, has enabled early prophylaxis in many children with poor venous access and has enabled the early start of home treatment with adequate injection frequency. Scoring systems for X-rays, magnetic resonance imaging, and function of joints were developed early in Sweden and have been widely disseminated worldwide, partly with modifications. Extended half-life products with half-life increased three to five times have been developed, which can provide superior bleed protection when dosed once-weekly and can maintain therapeutic trough levels when administered less frequently. The ultimate prophylaxis therapy in the future may be gene therapy.
Keywords: hemophilia A; hemophilia B; pediatric; prophylaxis; factor VIII; factor IX